2021
DOI: 10.1016/j.worlddev.2020.105212
|View full text |Cite
|
Sign up to set email alerts
|

Rural electrification and changes in employment structure in Cambodia

Abstract: We analyze the effect of electrification on changes in employment structure in Cambodia, which is still in early stage of electrification and structural change. In our analysis, we aim to examine the movement out of agriculture by looking into different categories of nonagricultural employment: nonagricultural self-employment, nonagricultural wage employment and nonagricultural unpaid workers. In order to mitigate the problem of non-random placement of electricity, we use the inverse probability of treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In this context, linked with Cubas Norando (2010) and Greenwood et al (2005), the results showed that the household purchases less technology if the women earned a lower salary than their created "value" at the house. As investigated by Dasso and Fernandez (2015), Tagliapietra et al (2020), and Chhay and Yamazaki (2021), this finding was also associated with the shift of occupations regarding the effect of household technology.…”
Section: Blue-collarmentioning
confidence: 76%
See 4 more Smart Citations
“…In this context, linked with Cubas Norando (2010) and Greenwood et al (2005), the results showed that the household purchases less technology if the women earned a lower salary than their created "value" at the house. As investigated by Dasso and Fernandez (2015), Tagliapietra et al (2020), and Chhay and Yamazaki (2021), this finding was also associated with the shift of occupations regarding the effect of household technology.…”
Section: Blue-collarmentioning
confidence: 76%
“…Few studies from developing countries revealed that household appliances significantly impact the employment of women with lower levels of education (Tewari & Wang, 2021). Recent studies from developing countries showed that access to electricity significantly affects nonagricultural employment (Chhay & Yamazaki, 2021;Tagliapietra et al, 2020). The mixed results of the studies revealed that household technology could provide the different outcomes of female labor supply with other occupations, education, and employment type.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations